First Language Interfere in EFL Classes: Revealing Students’ Perspectives and Teachers’ Reasons in ELL: - Liando, Nihta Vera Frelly; Tatipang, Devilito Prasetyo; Wuntu, Ceisy Nita (REiLA : Journal of Research and Innovation in Language, 2023)
Multilingualism is a common phenomenon among Indonesian students who are proficient in both national and local languages. However, the use of the first language (L1) in English as a Foreign Language (EFL) classrooms has been a subject of ongoing debate. This study explores the use of the first language (L1) in English as a Foreign Language (EFL) classrooms by investigating the perspectives of Indonesian students and teachers’ reasons. The study used a qualitative approach with a in-depth semi-structured interviews conducted with teachers, and questionnaire for the students, convenience sampling was used to select 105 participants from grade 12 of IPA, IPS, and Bahasa. Results showed that the majority of students had a positive perspective on the use of L1 by their English teachers during lessons. However, there was no significant difference in the students' perspectives based on gender and major classes. Teachers' reasons for using L1 included bridging students' knowledge, motivating students, and creating an active learning atmosphere. However, the overuse of L1 was found to be a potential problem, as it could lead to a lack of mastery of the target language. The findings suggest that the use of L1 in EFL classrooms can be beneficial but should be used in moderation to avoid students becoming too reliant on it. Teachers should use L1 as a means to facilitate learning, not as a substitute for the target language. This study provides important insights into the use of L1 in EFL classrooms from the perspectives of both students and teachers. These findings have important implications for language teaching practices and policies, not only in Indonesia but also in other multilingual contexts worldwide. Further research is needed to explore the long-term effects of L1 use on language acquisition and to develop effective strategies to minimize its negative impact.